2016
DOI: 10.1080/09593985.2016.1194653
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling movement and exercise with pain neuroscience education: A case for consistent education

Abstract: This article will introduce a conceptual framework of kinesthetic education that is consistent with and reinforces pain neuroscience education. This article will also provide some specific guidance for integrating pain neuroscience education with exercise and movement in a more congruent manner. Our belief is that this will enhance the effectiveness of specific movement approaches such as graded exposure techniques. Over the past decade, a new paradigm of pain education has been explored in an effort to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 86 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…The recommendation of the aerobic exercise and breathing combination is not only to increase fitness, but also to provide a way of controlling allodynia and hyperalgesia, which we are aware exists in patients with fibromyalgia. Controlling the pain limit with breathing seems to have an effect because patients who suffer from central pain, such as fibromyalgia [ 18 ], learn through this technique that reaching the point of pain is safe [ 19 , 20 , 21 ]. Deep slow breathing techniques decisively affect autonomic processing and pain thresholds [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation of the aerobic exercise and breathing combination is not only to increase fitness, but also to provide a way of controlling allodynia and hyperalgesia, which we are aware exists in patients with fibromyalgia. Controlling the pain limit with breathing seems to have an effect because patients who suffer from central pain, such as fibromyalgia [ 18 ], learn through this technique that reaching the point of pain is safe [ 19 , 20 , 21 ]. Deep slow breathing techniques decisively affect autonomic processing and pain thresholds [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The curative sector uses, for example, pain education and graded activity to target FOM and improve physical functioning. 34 , 35 , 36 It might be worthwhile to provide pain education in the management of MSDs at work to employees who struggle with FOM as well as to gradually increase their work activities. Next, our results show that FOM can influence the relationship between work‐related physical and psychosocial factors and MSDs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies focused on stress management and ergonomic training, where interventions such as exercise and advice to stay active showed promising results. The curative sector uses, for example, pain education and graded activity to target FOM and improve physical functioning 34‐36 . It might be worthwhile to provide pain education in the management of MSDs at work to employees who struggle with FOM as well as to gradually increase their work activities.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a complex experience that is influenced by many body systems, and the literature demonstrating the effectiveness of PNE on neuropathic pain is limited. A longitudinal study of 799 subjects by Lee et al demonstrated that 12 months after PNE alone, increased pain biology knowledge was associated with lower pain intensity and catastrophization [38] . Nonetheless, many argue that in isolation, the benefits of PNE are limited and must be accompanied by other interventions and/or physical activity under the guidance of a therapist for best results [39] .…”
Section: Pain Neuroscience Educationmentioning
confidence: 99%